Backstroke swimming: The effect of using hand paddles on swimming performance - Awad, M. A.; Aboalmaty, H.; Alreni, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It is recognised that the use of swimming aids such as hand paddles during training creates substantial improvement in swimming efficiency and performance (Abdelhameed and Hassaneen, 1997). This is a consequence of the improvement occurred to a specific power of the swimmers and the overall technique (Abu-Elella, 1994). Freestyle swimming has been extensively investigated with regard to the energy expenditure and biomechanical characteristics with hand paddles (Ogita et al., 1999; Elsokary et al., 2001). However, there is lake of information in the literature regarding the physiological demands and performance characteristics in backstroke swimming with hand paddles. Therefore, this study was undertaken to investigate the effect of using hand paddles on backstroke swimming`s technical characteristics and performance of Egyptian elite swimmers. Methods: Twelve Egyptian elite swimmers competing at the national and level on backstroke swimming style were included in this study. Data collection and measurements were performed in four different sessions with 3-days time interval. In each session, swimmers were requested to swim individually a 100-m backstroke with or without paddles at the same speed and level of intensity (100% of maximum speed). Results: Performance and stroke technical characteristics demonstrated lower stroke length, higher stroke number and gliding length without the use of hand paddles. The rating of perceived exertion (16.42 ± 2.8 vs 11 ± 2.84) was higher without the use of hand paddles. Discussion: This study investigated the effect of using hand paddles on the physiological and certain biomechanical characteristics of backstroke swimming on Egyptian elite swimmers. The finding indicated that backstroke swimming with hand paddles demonstrated significantly higher efficiency than without on Egyptian elite swimmers, which is consistent with the findings of Ogita and colleagues (1999).